The Characteristics of Road Traffic Fatalities in Kazakhstan's Semey Region, 2006-2010: A Descriptive Retrospective Study. - Ayan Myssayev; Serik Meirmanov; Tolebay Rakhypbekov; Tolkyn Bulegenov; Yuliya Semenova (Tehran University of Medical Sciences, 2014)
Kazakhstan, a developing middle-income country, has the highest road traffic collision (RTC) mortality in the European Region. The aims of this study were to determine main characteristics of road traffic fatalities in Semey region, Kazakhstan and to compare findings with National data and middle-income European countries.This descriptive surveillance study assesses RTC mortality rates and epidemiology in the Semey Region of East Kazakhstan Oblast. Data of all 318 road traffic fatalities form the Semey Regional Center for Forensic Medicine were analyzed for the 5-year period of January 1, 2006 through December 31, 2010.Over the study period, the average road traffic mortality in the Semey Region was 12.1 per 100,000 population with downward trend by 35.1% (p=0.002). The victims mean age was 37.1 (SD=17) years. Males predominated at 74.5%. Vehicle fatality was the most common mode of fatality at 61.3%. The majority of collisions, 53.1%, occurred on highways. Most victims, 67.3%, have died at the scene of collision; in 67.3% of fatalities, autopsies identified multiple injuries as cause of death. The high number of fatal collisions took place in "no snow" season (P